2020
DOI: 10.1007/s00429-020-02189-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ultrastructural localization of the glucagon-like peptide-1 receptor (GLP-1R) in the rat brain

Abstract: Glucagon-like peptide-1 (GLP-1) inhibits food intake and regulates glucose homeostasis. These actions are at least partly mediated by central GLP-1 receptor (GLP-1R). Little information is available, however, about the subcellular localization and the distribution of the GLP-1R protein in the rat brain. To determine the localization of GLP-1R protein in the rat brain, immunocytochemistry was performed at light and electron microscopic levels. The highest density of GLP-1R-immunoreactivity was observed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Other studies also indicated that GLP-1 directly stimulates the activity of POMC neurons [13]. As our recent ultrastructural studies [14] demonstrated that GLP-1R is present not only on the perikarya but also in a high number of axon terminals in the ARC, we raised the possibility that in addition to its direct effect on the POMC neurons, GLP-1 may also influence the POMC neurons indirectly by modulating the activity of the GLP-1-sensitive presynaptic terminals. To test this hypothesis, we performed ultrastructural studies to determine the relationship of the POMC neurons and the GLP-1R-IR structures and examined the effect of GLP-1 signaling on the inputs of the POMC neurons.…”
Section: Introductionmentioning
confidence: 76%
“…Other studies also indicated that GLP-1 directly stimulates the activity of POMC neurons [13]. As our recent ultrastructural studies [14] demonstrated that GLP-1R is present not only on the perikarya but also in a high number of axon terminals in the ARC, we raised the possibility that in addition to its direct effect on the POMC neurons, GLP-1 may also influence the POMC neurons indirectly by modulating the activity of the GLP-1-sensitive presynaptic terminals. To test this hypothesis, we performed ultrastructural studies to determine the relationship of the POMC neurons and the GLP-1R-IR structures and examined the effect of GLP-1 signaling on the inputs of the POMC neurons.…”
Section: Introductionmentioning
confidence: 76%
“…In the current study, we observed the following new findings. Previous studies have found that GLP-1Rs are expressed in various tissues, including the pancreatic islets, brain, dorsal root ganglia, and spinal cord [20,[40][41][42][43]. Regarding the cellular localization of GLP-1R in the CNS, there are controversial findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study by Farkas et al, 2020, localization of GLP-1R protein was determined in rat's brain. Immunoreactivity was seen in the circumventricular organs and areas around the arcuate nucleus and nucleus tractus solitarii (Farkas et al, 2020). Moreover, neuronal profiles of GLP-1R were distinguished in telencephalon, diencephalon, brainstem and cerebellum.…”
Section: Introductionmentioning
confidence: 97%